Association of Flu specific and SARS-CoV-2 specific CD4 T cell responses in SARS-CoV-2 infected asymptomatic heath care workers. Issue 41 (1st October 2021) - Pallikkuth, Suresh; Williams, Erin; Pahwa, Rajendra; Hoffer, Michael; Pahwa, Savita
Abstract: Influenza vaccination is widely advocated to avoid infection with influenza virus, a serious respiratory pathogen, and this was greatly emphasized during the raging COVID-19 epidemic. We conducted a study for baseline Flu specific immunity in a group of health care workers with documented past SARs-CoV-2 infection (designated COVID+) with mild or no symptoms and compared them with a control group that had not been infected with SARS CoV-2 (COVID-). Concurrently, we examined flu and SARS-CoV-2 specific T cell responses using the AIM (activation induced molecules) assay by flow cytometry. All COVID+ and 40% COVID- participants exhibited AIM responses to SARS-CoV-2 peptides, but only COVID+ were positive for SARs-CoV-2 antibody. Influenza HIN1 antigen specific CD4 T cells were found in 92% COVID+ and 76% COVID- participants and exhibited a strong direct correlation with SARS-CoV-2 specific CD4 T cells. This observation suggests that influenza specific T cell immunity may impact immune responses to SARS-CoV-2.